Kolokacje pronominalne jako źródło tożsamościowych odniesień (na materiale relacji świadków powstania warszawskiego) - Duda, Beata; Ficek, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The authors of the article present the results of (quantitative and qualitative) research on narrative interviews from the Oral History Archive – more precisely: memories of the Warsaw Uprising witnesses (its active participants). The main subject of the analyses, which align with the trends of reflections on the phenomenon of studies on social archives and follow the premises of memory linguistics, are the elements of the lexical level, i.e. collocations of the possessive pronouns mój, nasz (my, ours). In the discourse on the events of August 1944, they can be considered to be some of the significant determinants of individual and/or collective identities of the subjects. The search for answers to the questions about how the identity of the Warsaw Uprising participants is revealed at the level of selected biographical narrations, what elements dominate there and how it is determined, allows for drawing some conclusions, including the final one: despite the expected predominance of individual identity (and personal views of the past), the examined relationships show a strong expansion of the sense of community which is evident even in the areas that fall within the domain of individual memory.